2017
DOI: 10.1002/jbm.a.36267
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure in combination with topographical cues affects the fate of bone marrow‐derived human mesenchymal stem cells for bone tissue regeneration

Abstract: Topographical and mechanical cues are vital for cell fate, tissue development in vivo, and to mimic the native cell growth environment in vitro. To date, the combinatory effect of mechanical and topographical cues as not been thoroughly investigated. This study investigates the effect of PCL nanofiber alignment and hydrostatic pressure on stem cell differentiation for bone tissue regeneration. Bone marrow‐derived human mesenchymal stem cells were seeded onto standard tissue culture plastic and electrospun rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 62 publications
4
20
0
Order By: Relevance
“…This result is corroborated by other studies (Reinwald and El Haj, 2018;Zhao et al, 2015). Human BMSCs metabolic activity was upregulates by mechanical stimulation (270 kPa; 1 Hz stimulation for 1h per day, for 5 days out of 2 weeks) in comparison to the non-stimulated samples (Reinwald and El Haj, 2018). Moreover, it was shown that the application of hydrostatic pressure on rat BMSCs accelerates cell proliferation through upregulated cell cycle initiation (Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This result is corroborated by other studies (Reinwald and El Haj, 2018;Zhao et al, 2015). Human BMSCs metabolic activity was upregulates by mechanical stimulation (270 kPa; 1 Hz stimulation for 1h per day, for 5 days out of 2 weeks) in comparison to the non-stimulated samples (Reinwald and El Haj, 2018). Moreover, it was shown that the application of hydrostatic pressure on rat BMSCs accelerates cell proliferation through upregulated cell cycle initiation (Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…Osteoblasts responds to mechanical stimuli and remodel the bone architecture as a response (Lee and Volpicelli, 2017). In vivo, hydrostatic pressure is repeatedly stimulating bone cells and has shown to impact cell differentiation, makers expression and mineralisation of the bone tissue (Henstock et al, 2013;Huang and Ogawa, 2012;Reinwald and El Haj, 2018). As an emerging biomaterial in BTE (Lee et al, 2019), it is of importance to apply in vivo mechanical conditions to native cellulose scaffolds, as close matching of surrounding bone tissue as been shown to be the key factor in the success of alloplastic grafts (Gao et al, 2019;Nukavarapu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For mechanical stimulation, the bags were placed in a custom developed HP bioreactor and were subjected to an intermittent HP regime of 270 kPa and a frequency of 1 Hz for 1 h per day, 5 days per week for the duration of the study (21 days). A pressure of 270 kPa replicates the physiological pressures experienced by osteocytes in the lacunar-canalicular network of load-bearing bones (Zhang et al, 1998;Reinwald et al, 2015;Reinwald and El Haj, 2018). This pressure was found to promote bone growth and mineralization in a developmental model of organotypically cultured ex vivo chick fetal femurs (Henstock et al, 2013).…”
Section: Hydrostatic Pressure (Hp) Experimentsmentioning
confidence: 80%
“…Hydrostatic pressure is crucial for all tissues that transduce forces, such as those filled with fluids or highly hydrated, as their loading results in interstitial pressure modification (Reinwald and El Haj, 2018). A typical hydrostatic pressure bioreactor includes a chamber and a piston, which regulates its pressure.…”
Section: Hydrostatic Pressure and Compression Bioreactorsmentioning
confidence: 99%